Immunogenicity and safety of the 9-valent human papillomavirus vaccine in Chinese females 9–45 years of age: A phase 3 open-label study. Issue 23 (20th May 2022) - Lv, Huakun; Wang, Shenyu; Liang, Zhenzhen; Yu, Wei; Yan, Chuanfu; Chen, Yingping; Hu, Xiaosong; Fu, Rong; Zheng, Minghuan; Group, Thomas; Luxembourg, Alain; Liao, Xueyan; et al.
Highlights: The 9vHPV vaccine is currently approved for use in Chinese women aged 16–26 years. Immunogenicity was compared: 9–19- and 27–45- vs. 20–26-year-old Chinese females. Antibody responses were non-inferior in 9–19- and 27–45- vs. 20–26-year-olds. Data support bridging of efficacy to Chinese females aged 9–19 years and 27–45 years. The 9vHPV vaccine was generally well tolerated in Chinese females aged 9–45 years. Abstract: Background: The 9-valent human papillomavirus (9vHPV; HPV6/11/16/18/31/33/45/52/58) vaccine was approved for use in Chinese women aged 16–26 years in 2018. This phase 3, open-label study (NCT03903562) compared 9vHPV vaccine immunogenicity and safety in Chinese females aged 9–19 years and 27–45 years with Chinese females aged 20–26 years; we report results from day 1 through 1 month post-Dose 3. The study will continue through 54 months post-Dose 3 to assess antibody persistence in Chinese girls aged 9–19 years. Methods: Participants aged 9–45 years received three doses of the 9vHPV vaccine. Geometric mean titers (GMTs) and seroconversion percentages for anti-HPV6/11/16/18/31/33/45/52/58 antibodies were determined by competitive Luminex immunoassay in serum samples obtained at day 1 and 1 month post-Dose 3. Adverse events (AEs) within 30 days post-vaccination and serious AEs (SAEs) occurring at any time were recorded. Results: In total, 1990 participants (690 aged 9–19 years; 650 aged 20–26 years; 650 aged 27–45 years) were enrolled. At 1 month post-Dose 3, >99% of participants in the per-protocol immunogenicity population seroconverted to each vaccine HPV type. Anti-HPV6/11/16/18/31/33/45/52/58 antibody GMTs in the 9–19-year age group were non-inferior to those in participants aged 20–26 years. Anti-HPV6/11/16/18/31/33/45/52/58 seroconversion percentages in the 27–45-year age group were non-inferior to those in participants aged 20–26 years. Injection-site and systemic AEs were reported by 43.3% and 50.9%, 50.5% and 57.1%, and 43.8% and 43.4% of participants aged 9–19, 20–26, and 27–45 years, respectively. There were no vaccine-related SAEs, discontinuations due to AEs, and deaths. Conclusion: Antibody responses induced by 9vHPV vaccination in Chinese females aged 9–19 years and 27–45 years were non-inferior to those in Chinese females aged 20–26 years. The vaccine was generally well tolerated. ClinicalTrials.gov Identifier: NCT03903562.